67.6k views
4 votes
f(n)=93+4(n-1)f(n)=93+4(n−1)f, left parenthesis, n, right parenthesis, equals, 93, plus, 4, left parenthesis, n, minus, 1, right parenthesis Complete the recursive formula of f(n)f(n)f, left parenthesis, n, right parenthesis.

User Yacc
by
4.2k points

2 Answers

2 votes

Answer: f(n) = 4n + 97 (or 97 + 4n)

Explanation:

Distribute 4 and (n-1)

f(n) = 93 + 4n - 4

Add 93 and 4

f(n) = 97 + 4n

User Atyachin
by
4.7k points
5 votes

Answer:

The answer is 93 & 4

Explanation:

I got it right on khan. Btw I don't know if someone said this already bc I am sooo tired bc it's 1 am :(

User Nenad Bozic
by
5.2k points